THE EFFECT OF GOALS ON THE DEVELOPMENT OF THE YOUTH BASKETBALL PLAYERS’ CONTROL PLACE AND THE SOURCE OF MOTIVATION - Új, Eszter Dorottya; Csukonyi, Csilla; Őrsi, Balázs; Kiss, Brigitta (Stadium - Hungarian Journal of Sport Sciences, 2021)
Our study conducted research on the motivation of the basketball players of the Debrecen Basketball Academy (U11 - 76 basketball players) and on which factors play and define it, especially the control sites and their goals are related to the assessment of performance development. For this purpose, the target studies were based on such a follow-up procedure, which performs monitoring, and target studies on the development of physical endurance could be detected. Our results show that both the quality of choice (how complex tasks are undertaken with athletes in the study) and the evolution of the control site and the source of motivation are among the factors in developing athletes ’goals. The result showed that many objective measurement tools and test procedures are available to coaches and sport-psychologists to assess and evolve athletes’ peak performance. At the same time, further practical improvements can be made by changing training methods and introducing additional motivating factors.